Pengembangan Perangkat Pembelajaran Menggunakan Model Problem Posing Berorientasi Kemampuan Pemecahan Masalah Matematis - Resyania Aprilla Putri; Endang Istikomah; Aulia Sthephani; Zetriuslita Zetriuslita (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2021)
This study aims to describe the level of validity of mathematics learning tools using the Problem Posing model oriented to mathematical problem solving abilities on statistics which has been tested valid. The development model in this study uses the Plomp model which has three stage, namely the Preliminary Research Phase, the Prototype Phase, the Assessment Phase. The data collection techniques used were the validation of learning tools. The data collection instrument used was a validation sheet. The data analysis technique used is descriptive statiscal analysis technique. The result of the research validation analysis by three validators obtained an average validation every RPP of each validator was 100% for aspect of indicator one as measured by guttman scale of which are very valid criteria and 80,36% for aspect of indicator two to seven as measured by likert scale of which are valid criteria, and for the average validation every LKPD of each validator was 93,33% for aspect of indicator one as measured by guttman scale of which are very valid criteria and 75% aspect of indicator two to three as measured by likert scale of which are valid criteria. Based on the results of this study it can be concluded that the development of learning tools using the Problem Posing model oriented to the mathematical problem solving abilities has been tested for its validity.Keywords: LKPD, RPP, Problem Posing